2010 14th International Conference Information Visualisation 2010
DOI: 10.1109/iv.2010.61
|View full text |Cite
|
Sign up to set email alerts
|

Re-writing Recent History: Developing a National Reconciliation Pedagogy Using a Video Game for School Age Children

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Leveraging school-aged children's prior knowledge of using computer games, the reconciliation game provides a fun environment for students to explore complex concepts in a visually stimulating way. This paper expands on the background in this field reported in [13] and an earlier pilot study reported in [15].…”
Section: Introductionsupporting
confidence: 51%
“…Leveraging school-aged children's prior knowledge of using computer games, the reconciliation game provides a fun environment for students to explore complex concepts in a visually stimulating way. This paper expands on the background in this field reported in [13] and an earlier pilot study reported in [15].…”
Section: Introductionsupporting
confidence: 51%